Research advance of natural products in tumor immunotherapy - Huo, Jin-Ling; Fu, Wen-Jia; Liu, Zheng-Han; Lu, Nan; Jia, Xiang-Qian; Liu, Zhang-Suo (Frontiers in Immunology, 2022)
Cancer immunotherapy has emerged as a novel anti-tumor treatment. Despite significant breakthroughs, cancer immunotherapy remains focused on several types of tumors that are sensitive to the immune system. Therefore, effective strategies to expand its indications and improve its efficacy become key factors for the further development of cancer immunotherapy. In recent decades, the anticancer activities of natural products are reported to have this effect on cancer immunotherapy. And the mechanism is largely attributed to the remodeling of the tumor immunosuppressive microenvironment. The compelling data highlight that natural products offer an alternative method option to improve immune function in the tumor microenvironment (TME). Currently, more attention is being paid to the discovery of new potential modulators of tumor immunotherapy from natural products. In this review, we describe current advances in employing natural products and natural small-molecule drugs targeting immune cells to avoid tumor immune escape, which may bring some insight for guiding tumor treatment.